A comparative study of in clinico-pathological profile in dengue shock syndrome versus other types children’s at tertiary health care center - Shah, Bhavesh; Phirke, Deepa Sachin (International Journal of Research in Medical Sciences, 2017)
Background: Dengue a mosquito borne arboviral disease is caused by one of the serotypes of dengue virus (DEN-1, DEN-2, Den-3, DEN-4) belonging to the family Flaviviridae. The objective of this study was to study clinco-pathological profile of Dengue shock syndrome versus Other types children’s at tertiary health care center. Methods: This was Cross sectional observational study was conducted in a tertiary care hospital in the Department of Pediatrics after obtaining approval from the institutional Ethical Committee. The study was carried out over a period of one & half years from January 2015 to June 2016 Statistical analysis done by Chi-square, ANOVA, Paired t test SPSS version 22 (IBM SPSS Statistics, Somers NY, USA) was used to analyze data. Results: Mean age of patients were 8.08±2.72 years, majority of cases were females (51.9%) and 48.1% were males, the clinical features like hepatomegaly, Ascites Pleural Effusion significantly present in DSS (P<0.001). In the study, there was no significant difference in symptoms and severity of dengue fever except for convulsion Thrombocytopenia (platelet<1lakh/cmm) was observed in 74% of cases, leucopenia (total leukocyte count <4000/cmm) was observed in 56% of cases, haemocrit more than 40 was observed in 21.27% cases. Dengue shock syndrome had acute kidney injury, CCF and encephalopathy. This observation of complications between dengue severity was statistically significant. There was significant difference in haematocrit values between three diagnoses of dengue fever from day 1 till day 4. Initially higher haematocrit was observed in Dengue shock syndrome, later goes on decreasing. Conclusions: It can be concluded from our study that significantly dengue shock syndrome had acute kidney injury, CCF and encephalopathy. There was significant difference in hematocrit values between three diagnoses of dengue fever from day 1 till day 4. Initially higher hematocrit was observed in dengue shock syndrome.